Tandem processes promoted by a hydrogen shift in 6-arylfulvenes bearing acetalic units at ortho position: a combined experimental and computational study - Mateo Alajarin (Beilstein Journal of Organic Chemistry, 2016)
6-Phenylfulvenes bearing (1,3-dioxolan or dioxan)-2-yl substituents at ortho position convert into mixtures of 4- and 9-(hydroxy)alkoxy-substituted benz[f]indenes as result of cascade processes initiated by a thermally activated hydrogen shift. Structurally related fulvenes with non-cyclic acetalic units afforded mixtures of 4- and 9-alkoxybenz[f]indenes under similar thermal conditions. Mechanistic paths promoted by an initial [1,4]-, [1,5]-, [1,7]- or [1,9]-H shift are conceivable for explaining these conversions. Deuterium labelling experiments exclude the [1,4]-hydride shift as the first step. A computational study scrutinized the reaction channels of these tandem conversions starting by [1,5]-, [1,7]- and [1,9]-H shifts, revealing that this first step is the rate-determining one and that the [1,9]-H shift is the one with the lowest energy barrier.